2012
DOI: 10.1371/journal.pone.0036090
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas viridiflava, a Multi Host Plant Pathogen with Significant Genetic Variation at the Molecular Level

Abstract: The pectinolytic species Pseudomonas viridiflava has a wide host range among plants, causing foliar and stem necrotic lesions and basal stem and root rots. However, little is known about the molecular evolution of this species. In this study we investigated the intraspecies genetic variation of P. viridiflava amongst local (Cretan), as well as international isolates of the pathogen. The genetic and phenotypic variability were investigated by molecular fingerprinting (rep-PCR) and partial sequencing of three ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 49 publications
2
42
0
2
Order By: Relevance
“…They appear to provide a sound method for classification of Pseudomonas strains isolated from cucumber. The gyrB-based phylogenetic tree for the local isolates was topologically almost identical to the tree based on the rep-PCR fingerprinting, while the phylogenetic tree based on the rpoB and rpoD gene sequences revealed clearly different patterns of variation (Sarris et al 2012). Our results indicate that although the gyrB is indeed one of the best markers for P.syringae pv.…”
Section: Discussionsupporting
confidence: 53%
“…They appear to provide a sound method for classification of Pseudomonas strains isolated from cucumber. The gyrB-based phylogenetic tree for the local isolates was topologically almost identical to the tree based on the rep-PCR fingerprinting, while the phylogenetic tree based on the rpoB and rpoD gene sequences revealed clearly different patterns of variation (Sarris et al 2012). Our results indicate that although the gyrB is indeed one of the best markers for P.syringae pv.…”
Section: Discussionsupporting
confidence: 53%
“…However, several bacterial species have been reported to cause Solanaceae ‘pith necrosis’ in Greece, including P. cichorii (Trantas et al ., ), P. corrugata (Alivizatos, ), P. viridiflava (Malathrakis & Goumas, ; Sarris et al ., ) and P . fluorescens (Malathrakis & Goumas, ), and also members of the Pectobacterium genus (previously named Erwinia ) P. atrosepticum and P. carotovorum (Malathrakis & Goumas, ), and Dickeya chrysanthemi (Alivizatos, ).…”
Section: Discussionmentioning
confidence: 91%
“…The initial screening of 72 bacterial strains from the TEIC bacterial collection revealed that 32 of them exhibited the characteristic P. corrugata wrinkled colony formation when grown on NA supplemented with 1% glucose, and these were subjected to further biochemical and phytopathological characterization. The remaining bacterial isolates belonged mainly to P. viridiflava and P. cichorii species and have been characterized previously from this group (Sarris et al ., ; Trantas et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the well‐established heterogeneity within phylogroups of P. syringae , P. viridiflava has been reported to be relatively homogeneous (Sarris et al ., ). Although designated with a species name, P. viridiflava represents one of the multiple phylogroups found within the P. syringae species complex (Gardan et al ., ; Mulet et al ., ; Parkinson et al ., ).…”
Section: Introductionmentioning
confidence: 99%